MMS Observations of Electrostatic Waves in an Oblique Shock Crossing. Issue 11 (28th November 2018) - Goodrich, Katherine A.; Ergun, Robert; Schwartz, Steven J.; Wilson, Lynn B.; Newman, David; Wilder, Frederick D.; Holmes, Justin; Johlander, Andreas; Burch, James; Torbert, Roy; Khotyaintsev, Yuri; Lindqvist, Per‐Arne; et al.
Abstract: High‐resolution particle and wave measurements taken during an oblique bow shock crossing by the Magnetospheric Multiscale (MMS) mission are analyzed. Two regions of differing magnetic behavior are identified within the shock, one with active magnetic fluctuations and one with laminar interplanetary magnetic field topology. A prominent reflected ion population is observed in both regions. The active magnetic region is characterized by large‐amplitude (>100 mV/m) electrostatic solitary waves, electron Bernstein waves, and ion acoustic waves, along with intermittent current activity and localized electron heating. In the region of laminar magnetic field, ion acoustic waves are prominently observed. Solar wind ion deceleration is observed in both regions of active and laminar magnetic field. All observations suggest that solar wind deceleration can occur as a result of multiple independent processes, in this case current and ion‐ion instabilities. Key Points: Two regions of the shock are observed, one with active magnetic field fluctuations and one with laminar magnetic field The presence of both current instabilities and ion‐ion instabilities is observed in different regions of the shock Solar wind ions are observed to be decelerated in laminar magnetic field in the presence of ion acoustic waves